31 Cyopreservation and recovery of thymus tissue prior to transplantation into paediatric patients with DiGeorge syndrome. (22nd November 2019) - Kelly, Paul; Obiri-Yeboa, Irene; Marriott, Clare; Howley, Evey; Kreins, Alexandra; Gilmour, Kimberly C; Buckland, Matthew; Davies, Graham
Abstract : Thymus transplantation is indicated for the treatment of athymia and associated T cell deficiency in patients with DiGeorge syndrome. HLA matching of donor and recipient is currently limited by availability of donor thymus tissue immediately prior to transplant and the effect of unmatched transplanted tissue on immune reconstitution remains unknown. We hypothesize that successful cryopreservation and recovery of tissue will allow for biobanking of thymus tissue, permitting HLA matching between donor and recipient and ultimately improved levels of immune reconstitution. Donor thymus tissue is routinely removed during paediatric cardiac surgery and made available for the transplant programme. The thymus tissue is subsequently decapsulated and sliced into 2 mm sections under clean room conditions. These sections were cultured for 24 hours before cryopreservation using a commercially available freezing solution in a controlled rate freezer at a rate of -1°C/minute until reaching -100°C. Upon reaching temperature the tissue sections were transferred to liquid nitrogen for long term storage. Prior to transplantation, sections were recovered by defrosting in a 37°C incubator followed by 2 washes in culture media to remove the freezing solution. The thymus sections were then cultured for 14-21 days until transplantation to deplete donor lymphocytes. Histological analysis indicated the thymus tissue remained viable following cryopreservation and recovery, with only a 5-10% loss of viable epithelium (n=4). Transplantation of cryopreserved tissue alongside fresh tissue into patients with DiGeorge syndrome is now underway. Future work will examine if the transplanted cryopreserved tissue can support thymopoeisis via a biopsy obtained at 3 months post-transplant and ultimately levels of immune reconstitution will be examined in patients transplanted with either fresh or cryopreserved tissue.